2013
DOI: 10.1111/coa.12099
|View full text |Cite
|
Sign up to set email alerts
|

Deviated nose attenuates the degree of patient satisfaction and quality of life in rhinoplasty: a prospective controlled study

Abstract: Rhinoplasty can provide an objective improvement, high satisfaction and positive impact on quality of life. However, the degree of satisfaction and improvement in quality of life in patients with deviated nose deformity are less than patients with non-deviated nose deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Opposingly, Cingi and Eskiizmir found that postoperative satisfaction in patients with nondeviated nasal deformities improves to a greater degree than those with deviated noses. 20 In another study, Cingi et al 27 found that patients have equal improvements in satisfaction following primary and secondary rhinoplasty. As such, it is important for future work to further study how the aforementioned factors interplay with structural and dorsal preservation surgical techniques with regard to overall patient satisfaction after rhinoplasty.…”
Section: Resultsmentioning
confidence: 97%
“…Opposingly, Cingi and Eskiizmir found that postoperative satisfaction in patients with nondeviated nasal deformities improves to a greater degree than those with deviated noses. 20 In another study, Cingi et al 27 found that patients have equal improvements in satisfaction following primary and secondary rhinoplasty. As such, it is important for future work to further study how the aforementioned factors interplay with structural and dorsal preservation surgical techniques with regard to overall patient satisfaction after rhinoplasty.…”
Section: Resultsmentioning
confidence: 97%
“…1,9,10 Furthermore, rhinoplasty was found to significantly increase the quality of life in terms of an improved satisfaction with appearance, self-confidence, and social interaction. [11][12][13][14] With a proper preoperative assessment, patients are expected to be satisfied both functionally and psychosocially. 12,15 However, many deformities such as hooked or saddle noses are more apparent when observed from a full profile view.…”
mentioning
confidence: 99%
“…Cingi and Eskiizmir used the European Quality of Life–5 Dimension (EQ‐5D) questionnaire. Their results showed high satisfaction and a positive impact on their patients' quality of life, as the mean EQ‐5D index was raised to 0.93 ± 0.20 postoperatively from 0.34 ± 0.29 preoperatively.…”
Section: Discussionmentioning
confidence: 99%